Unconventional use of ablative fractional photothermolysis in arm contouring. (2nd April 2020) - Ellis, Morgan M.; Scott, Jennifer L.; DeKlotz, Cynthia Marie Carver
ABSTRACT: Brachioplasty, in addition to several nonsurgical interventions (e.g. cryolipolysis, noninvasive radiofrequency, and intense-focused ultrasound) have been described as efficacious in the elimination of excess skin laxity from the upper arms. Recently, fractional CO2 ablation has gained attention for its ability to reduce rhytids and improve skin texture on the face, neck, and hands. In this article, we report the first successful case of fractional CO2 ablation for upper arm contouring.